Survey of job burnout and depression in standardized residency training programs in China. Issue 35 (August 2019) - Zhang, Yun; Chu, Xiaotian; Sha, Yue; Zeng, Xuejun; Shen, Ti
Abstract : Abstract: To evaluate job burnout and its impacts on mental health among clinical residents in a 3-year standardized residency training program in China. This cross-sectional study was conducted among all residents in the Department of Internal Medicine of the Peking Union Medical College Hospital in August 2017. Job burnout and depressive symptoms were assessed using the Maslach Burnout Inventory-General Survey and the Center for Epidemiological Survey, Depression, respectively. Among the 159 residents who completed the survey, comprising 69 who had graduated from 8-year medical schools and 90 from 5-year schools, the rate of job burnout was 62.2% (100/159) and the rate of depression was 28.3% (45/159). Rates of job burnout and depression in residents completed different years of training showed no significant difference. Rate of job burnout was significantly higher among graduates of 5-year medical schools (76.7%) than among those of 8-year schools (44.9%, P < .001). Pearson chi-squared test revealed a significant correlation between depression and job burnout ( P < .001). Multiple logistic regression revealed a significant correlation between job burnout and attendance at 5- or 8-year medical schools ( P = .044). Job burnout may be more frequent among graduates from 5-year medical schools than among those from 8-year schools.